Objectively measured physical activity of Vietnamese adults with type 2 diabetes: Opportunities to intervene - Jancey, Jonine; Lee, Andy; Van Do, V.; Pham, N.; Nguyen, C.; Van Hoang, M. (2019)
Objectives: To objectively determine and compare the physical activity (PA) levels of adults newly diagnosed with type 2 diabetes (T2D) and adults without T2D in Vietnam using an accelerometer. Methods: A total of 120 participants with newly diagnosed T2D and 120 adults without T2D were recruited from a large hospital in Hanoi, the capital city of Vietnam. All participants wore an ActiGraph GT3X accelerometer for at least 5 days, including 1 weekend day. Freedson cut-off points were used to estimate different intensities of PA. In addition, comparisons between groups were made with respect to achieving the World Health Organization (WHO) and International Diabetes Federation (IDF) recommended PA guidelines. Results: Men with T2D had significantly lower levels of PA than men without T2D. The respective multivariable-adjusted mean values of daily step count, daily light-intensity, moderate-intensity, and moderate-to-vigorous-intensity PA were approximately 14%, 19%, and 22% lower in the men with T2D than in their non-T2D counterparts. However, women with T2D accumulated a greater number of steps per day than women without T2D. Only 59.2% of the adults with T2D met the minimum recommended level of PA (WHO and IDF), compared to 74.2% of adults without T2D (p<0.05). After adjusting for potential confounders, participants with T2D experienced 50.0% significantly lower odds of achieving PA recommendations. Conclusions: Vietnamese men with T2D were less physically active than those without T2D, and adults with T2D were less likely to meet PA guidelines. The results suggest a need for integrating PA into the self-management of this chronic condition.